HYPONYMIC RELATIONS IN RAILWAY TERMINOLOGY AND ENSURING SEMANTIC CORRESPONDENCE IN TRANSLATION (SCIENCE TIME JOURNAL, 2026)
This paper examines hyponymic relations — hierarchical genus-species semantic structures — within English and Uzbek railway terminology, and analyses the challenges these structures pose for achieving semantic correspondence in translation. Hyponymy organises technical vocabulary into taxonomic chains in which a superordinate term (hypernym) covers a class of more specific terms(hyponyms), and the translational task requires not only finding formal equivalents but reproducing the correct level of specificity. Drawing on bilingual documentation from Uzbekistan Railways, UIC multilingual terminology resources, and a comparative corpus of English and Uzbek railway technical texts, the study identifies three principal translation problems arising from hyponymic asymmetry: